2017
DOI: 10.1177/2325967117699816
|View full text |Cite
|
Sign up to set email alerts
|

Medial Patellar Instability: Treatment and Outcomes

Abstract: Background:Historically, a lateral retinacular release was one of the primary surgical interventions used to treat lateral patellar instability. However, disruption of the lateral structures during this procedure has been associated with medial instability of the patella.Hypothesis:We hypothesize that good to excellent outcomes can be achieved at midterm follow-up after lateral patellotibial ligament reconstruction.Study Design:Case series; Level of evidence, 4.Methods:Thirteen patients were treated for medial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Multiple techniques for reconstruction of the lateral patellar stabilizers have been described, illustrating the need for a thorough anatomy study. 19,24,25 Reports on clinical outcomes after LPFL reconstruction have had a recent surge in the literature and are often described in the setting of previous lateral retinaculum release complicated by iatrogenic medial patellar instability. Multiple case series have included beneficial outcomes after LPFL reconstruction in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple techniques for reconstruction of the lateral patellar stabilizers have been described, illustrating the need for a thorough anatomy study. 19,24,25 Reports on clinical outcomes after LPFL reconstruction have had a recent surge in the literature and are often described in the setting of previous lateral retinaculum release complicated by iatrogenic medial patellar instability. Multiple case series have included beneficial outcomes after LPFL reconstruction in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Moatshe et al. 10 published a case series of 13 knees using a technique combining autograft lateral patellar tendon and ITB, showing improvement in Lysholm and Western Ontario and McMaster Universities Arthritis Index scores at 2 years postoperatively with a mean satisfaction of 8.2/10. Sanchis-Alfonso et al.…”
Section: Discussionmentioning
confidence: 99%
“…A few retrospective studies have looked at outcomes in LPFL reconstruction. Moatshe et al 10 published a case series of 13 knees using a technique combining autograft lateral patellar tendon and ITB, showing improvement in Lysholm and Western Ontario and McMaster Universities Arthritis Index scores at 2 years postoperatively with a mean satisfaction of 8.2/10. Sanchis-Alfonso et al 8 reported on 17 knees at 18 to 48 months postoperatively using ITB autograft and found similarly improved Lysholm scores and improved psychometrics postoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to recognize pediatric patients with congenital (fixed) or obligatory (habitual) patellar dislocations as these patients often require extensive bony realignment and soft tissue tensioning procedures with better outcomes when performed at a younger age [80]. Furthermore, in rare cases, patients may suffer from medial patellar instability in the setting of an acute traumatic dislocation or secondary to iatrogenic damage to lateral sided structures (i.e., isolated lateral release) necessitating alternative forms of surgical intervention [81,82].…”
Section: Additional Considerationsmentioning
confidence: 99%